PENGARUH KEGIATAN LUKIS TIUP TERHADAP PERKEMBANGAN KREATIVITAS KARYA SENI ANAK USIA DINI KELOMPOK B DI TK KANTIL : THE INFLUENCE OF BLOW PAINTING ACTIVITIES ON THE DEVELOPMENT OF CREATIVITY OF ART WORKS OF EARLY AGE CHILDREN IN GROUP B IN KANTIL KINDERGARTEN - Intan Nia Indriani; Juli Yanti Harahap (Program Studi PG-PAUD Universitas PGRI Adi Buana Surabaya, 2023)
The formulation of the problem in this study is whether there is an influence of blow painting activities on the development of creativity in group B early childhood art at Kantil Kindergarten T.A 2022/2023. The purpose of this study was to determine the effect of blow painting activities on the development of artistic creativity in group B early childhood at Kantil Kindergarten T.A 2022/2023. This study used a quantitative method (experimental) with a pre-experimental design, namely one group pretest-posttest design. The population in this study amounted to 22 children who were early childhood aged 4-5 years in group A and early childhood aged 5-6 in group B. The sample in this study were children aged 5-6 years in group B, totaling 15 children. . Data collection techniques using observation sheets. Data analysis techniques use statistical tests, namely data normality tests and hypothesis testing using the t-test. Based on the results obtained, it can be concluded that there is a significant influence of blow painting activities on the creativity of early childhood artwork. This is based on the results of the t-test, obtained Tcount = 4.212 and Ttable = 1.761. Therefore it can be concluded that Tcount>Ttable (4.212>1.761) which means Ho is rejected and Ha is accepted